DISCOVERY OF A GLOBAL TECTONIC WAVE FRONT IN SHOT-INDUCED SEISMIC WAVE TRAINS PASSING THROUGH THE EARTH - Lyuke Y.I.; An V.A.; Pasechnik I.P. (My University, 1988)
The authors analyze time series recorded at stations located in Eurasia and North America and produced by explosions in Nevada (N) and Kazakhstan (K). The series were recorded at epicentral distances Δ ranging from 1° to 91° and are between 12 and 20 years in length. The objective is to determine how the variations noted propagate in the lithosphere of the Northern Hemisphere. It was found that based on available observational data, it is most probable that peaks in the time series are phases of a tectonic wave which in the Northern Hemisphere propagates at about 300 km/year in the meridional direction. This assertion does not foreclose the possibility that in some regions there may exist waves with other velocities and orientations governed by the regional structural characteristics of the crust and mantle.